Feasibility of foot deformations corrective operations performing in patients with diabetes - S. D. Shapoval; I. L. Savon; O. V. Tribushnoy; V. O. Byelinska; O. O. Maksimovа (Zaporožskij Medicinskij Žurnal)
Objective: To improve methods of early diagnosis of diabetic neuropathy and suggest options for surgical prophylaxis possible purulent and necrotic complications in patients with diabetic foot syndrome.